Treatment with a Ginkgo biloba extract, EGb 761, inhibits excitotoxicity in an animal model of spinocerebellar ataxia type 17 - Huang DS; Lin HY; Lee-Chen GJ; Hsieh-Li HM; Wu CH; Lin JY (Drug Design, Development and Therapy, 2016)
Ding-Siang Huang,1,* Hsuan-Yuan Lin,1,2,* Guey-Jen Lee-Chen,1 Hsiu-Mei Hsieh-Li,1 Chung-Hsin Wu,1 Jung-Yaw Lin1,21Department of Life Science, National Taiwan Normal University, 2Institute of Biochemistry and Molecular Biology, National Taiwan University, Taipei City, Taiwan, Republic of China*These authors contributed equally to this workAbstract: Spinocerebellar ataxia type 17 (SCA 17) is a polyglutamine disease caused by the expansion of CAG/CAA repeats in the TATA box-binding protein (TBP) gene. The Ginkgo biloba extract, EGb 761, contains flavonoids and terpenoids with a potential use for the treatment of neurodegenerative diseases such as Alzheimer’s and Parkinson’s diseases. The neuroprotective effects of EGb 761 are obvious, but whether the EGb 761 has therapeutic effects in SCA 17 is still unclear. To manage our issues, we have generated TBP/79Q-expressing SH-SY5Y cells and SCA 17 transgenic mice with the mutant hTBP gene. In in vitro experiment, we observed that the EGb 761 treatment decreased the amount of sodium dodecyl sulfate-insoluble proteins in the TBP/79Q-expressing SH-SY5Y cells. We further found that the EGb 761 treatment could inhibit excitotoxicity and calcium influx and reduce the expression of apoptotic markers in glutamate-treated SH-SY5Y neuroblastoma cells. In in vivo experiment, we observed that the EGb 761 treatment (100 mg/kg intraperitoneal injection per day) could relieve the motor deficiencies of the SCA 17 transgenic mice. Our findings provide evidence that the EGb 761 treatment can be a remedy for SCA 17 via suppressing excitotoxicity and apoptosis in SCA 17 cell and animal models. Therefore, we suggest that EGb 761 may be a potential therapeutic agent for treating SCA 17.Keywords: spinocerebellar ataxia type 17, excitotoxicity, EGb 761, polyQ diseases, apoptosis